Electrospun Silk Fibroin Scaffolds for Tissue Regeneration: Chemical, Structural, and Toxicological Implications of the Formic Acid-Silk Fibroin Interaction - Biagiotti, Marco; Bassani, Giulia Alessandra; Chiarini, Anna; Vincoli, Valentina Teodolinda; Dal Prà, Ilaria; Cosentino, Cesare; Alessandrino, Antonio; Taddei, Paola; Freddi, Giuliano (Frontiers in Bioengineering and Biotechnology, 2022)
The dissolution of Bombyx mori silk fibroin (SF) films in formic acid (FA) for the preparation of electrospinning dopes is widely exploited to produce electrospun SF scaffolds. The SilkBridge® nerve conduit is an example of a medical device having in its wall structure an electrospun component produced from an FA spinning dope. Though highly volatile, residual FA remains trapped into the bulk of the SF nanofibers. The purpose of this work is to investigate the type and strength of the interaction between FA and SF in electrospun mats, to quantify its amount, and to evaluate its possible toxicological impact on human health. The presence of residual FA in SF mats was detected by FTIR and Raman spectroscopy (new carbonyl peak at about 1725 cm-1) and by solid-state NMR, which revealed a new carbonyl signal at about 164.3 ppm, attributed to FA by isotopic 13C substitution. Changes occurred also in the spectral ranges of hydroxylated amino acids (Ser and Thr), demonstrating that FA interacted with SF by forming formyl esters. The total amount of FA was determined by HS-GC/MS analysis. The greatest part was present as formyl ester, a small part (about 3%) as free FA. Approximately 17% of the Ser and Thr OH groups were involved in the formation of formyl esters. Treatment with alkali (Na2CO3) succeeded to remove the greatest part of FA, but not all. Alkali-treated electrospun SF mats underwent morphological, physical, and mechanical changes. The average diameter of the fibers increased, the mat shrunk, became stiffer, and lost elasticity. Biocompatibility studies with human adult dermal fibroblasts did not show a significant difference in cell proliferation and metabolic activity between untreated and alkali-treated electrospun mats. An in-depth evaluation of the possible toxicological impact of residual FA was made using the SilkBridge® nerve conduit as a case study, following the provisions of the ISO 10993-1 standard. The results showed that the amount of FA left on SF mats after electrospinning does not raise concerns for human health.